Athlete psychological resilience and integration with digital mental health implementation amid Covid-19 - Balcombe, L.; De Leo, D. (2021)
The current pandemic`s effect on mental health is uncertain with reports of it being largely negative related to loneliness and unemployment. There are different responses to pandemic stress with regards to cultural differences and social environment. Athletes are special in their experience of psychological resilience - there is a trend of positive adjustment to adversity and stress. However, further systematic review is required to confirm these findings along with an athlete-specific psychological resilience instrument. Key themes in relationships include a dichotomous mental health state marked by maladjustment and subsequent resilience, biopsychosocial factors as well as an array of cultural, social and environmental support and demands marked by stressors within and outside of sport. Digital mental health implementation is a logical next step for advancing the construct of athlete psychological resilience towards complementing an effective prevention and early intervention. However, mental health practitioners are grappling with digital mental health in a hybrid model of care. There is a need for converging on methodologies due to the rapid development of digital technologies which have outpaced evaluation of rigorous digital mental health interventions. The functions and implications of human and machine interactions require explainable and responsible implementation for more certain and positive outcomes to arise.